Improving Understanding And Learning Activities Of Simple Present Tense Declarative Sentences Through Whatsapp-Based Substitution Drills Techniques For Mtsn Students In Kupang City - Mohammad Yani Pehang; Darmanto Minggele; Hanif Cahyo Adi Kistoro (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Background: Students' understanding of the subject matter is a process of learning activities. Purpose: This study aims to determine the increase in understanding of simple declarative sentence material. present tense through substitution technique drills based on whatsapp application. Design/methods/approach: This type of research is classroom action research (CAR) which is motivated by the lack of activity and understanding of class VIII G MTsN Kupang City students in the 2020/2021 academic year related to the material of simple present tense declarative sentences which is implemented with an online learning system. Based on pre-cycle data, it is known that there are 66.66% or 20 students who do not understand simple present tense declarative sentences through guided substitution drills technique . Data collection of learning activities was carried out using observation techniques, while student understanding data was collected using test techniques. Observation data were analyzed qualitatively (descriptive narrative) while learning outcome data were analyzed quantitatively by determining the average, frequency, range, and percentage of classical completion . Findings: The results of the study showed that there was an increase in activity and learning outcomes in each cycle, from the initial/pre-cycle conditions which recorded only 34% of active students with classical completion of 60% (knowledge), increasing to 60% of active students with classical completion of 75% (knowledge aspect) in cycle I , and in cycle II there were 86.66% active students with classical completion of 90% in both knowledge and skills aspects . In line with the research results, it is concluded that the application of the substitution technique Drills can improve English activity and understanding of declarative material. sentence simple present tense in class VIII G students of MTsN Kota Kupang in the 2020/2021 academic year . Research implications/limitations: The main suggestion proposed for teachers is to can use the substitution technique drill in optimizing the learning process on the material of simple present tense declarative sentences . Originality/value: The novelty of research in the field of language needs to be developed more widely by other researchers both in terms of content, scope of study, and research design.